Influence of laboratory animal hosts on the life cycle of Hyalomma marginatum and implications for an in vivo transmission model for Crimean-Congo hemorrhagic fever virus - GARGILI KELEŞ, AYŞEN (FRONTIERS MEDIA SA, 2013)
Crimean-Congo hemorrhagic fever virus (CCHFV) is one of the most geographically widespread arboviruses and causes a severe hemorrhagic syndrome in humans. The virus circulates in nature in a vertebrate-tick cycle and ticks of the genus Hyalomma are the main vectors and reservoirs. Although the tick vector plays a central role in the maintenance and transmission of CCHFV in nature, comparatively little is known of CCHFV-tick interactions. This is mostly due to the fact that establishing tick colonies is laborious, and working with CCHFV requires a biosafety level 4 laboratory (BSL4) in many countries. Nonetheless, an in vivo transmission model is essential to understand the epidemiology of the transmission cycle of CCHFV. In addition, important parameters such as vectorial capacity of tick species, levels of infection in the host necessary to infect the tick, and aspects of virus transmission by tick bite including the influence of tick saliva, cannot be investigated any other way. Here, we evaluate the influence of different laboratory animal species as hosts supporting the life cycle of Hyalomma marginatum, a two-host tick. Rabbits were considered the host of choice for the maintenance of the uninfected colonies due to high larval attachment rates, shorter larval-nymphal feeding times, higher nymphal molting rates, high egg hatching rates, and higher conversion efficiency index (CEI). Furthermore, we describe the successful establishment of an in vivo transmission model for CCHFV in a BSL4 biocontainment setting using interferon knockout mice. This will give us a new tool to study the transmission and interaction of CCHFV with its tick vector.
Keywords: Crimean-Congo hemorrhagic fever; Hyalomma marginatum; BSL4; transmission; Crimean-Congo hemorrhagic fever virus; bunyavirus; tick; tick-borne virus; IMPELTATUM ACARI; TRUNCATUM ACARI; IMMATURE STAGES; 1844 IXODOIDEA; IXODIDAE; KOCH; REPLICATION; OVIPOSITION; RUFIPES; TICKS